The jurisprudential study of psychological warfare from Imam's point of view - M. M. Ahmadi, H. Chavoshi (Opción, 2019)
Today, more than ever, the importance of psychological warfare has been high and takes place in a different format. And considering the importance of this issue in the current situation,psychological warfareis discussed in this article, its dimensionshave been examinedand explored from jurisprudence point of view. In this study, through using Qur’an andnarrative texts, the necessity of psychological warfarehas been proven with the legal and ethical obligation against the enemy, in addition to verses about proving psychological warfare, rational reasons, the consensus of scholars of Islam and the traditions have been used in this regard.